2019
DOI: 10.4236/psych.2019.1015133
|View full text |Cite
|
Sign up to set email alerts
|

Parental Socialization of Emotion: Differences in Mothers of Children with and without Intellectual Disability

Abstract: Children with intellectual disabilities (ID) present developmental deficits in socio-emotional competencies compared to same-aged children with typical development (TD). Parents play a crucial role in fostering the socio-emotional development of their children, yet, few studies have investigated the socialization of emotion by parents of children with ID. In the current study, 34 mothers of children with ID and those with children with TD (40) completed questionnaires and were compared on their socialization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It would therefore be interesting to explore the empathy profile of these children. Given the specific emotion-related socialization behaviors of parents of children with IDs ( Rodas et al, 2016 ; Jacobs et al, 2019b ; Légaré et al, 2019 ), it would be interesting to consider family environment in this kind of study: parental socialization of emotions (e.g., reactions and conversations) has been recently found to affect social adjustment ( Jacobs et al, 2019b ), emotion regulation, and ToM abilities ( Jacobs et al, 2019a ). To investigate more precisely the causal contribution of ToM and SIP to each other and to the social and emotional competence of children with IDs, longitudinal studies or experimental studies implementing ToM or SIP training need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would therefore be interesting to explore the empathy profile of these children. Given the specific emotion-related socialization behaviors of parents of children with IDs ( Rodas et al, 2016 ; Jacobs et al, 2019b ; Légaré et al, 2019 ), it would be interesting to consider family environment in this kind of study: parental socialization of emotions (e.g., reactions and conversations) has been recently found to affect social adjustment ( Jacobs et al, 2019b ), emotion regulation, and ToM abilities ( Jacobs et al, 2019a ). To investigate more precisely the causal contribution of ToM and SIP to each other and to the social and emotional competence of children with IDs, longitudinal studies or experimental studies implementing ToM or SIP training need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…More particularly, perspective-taking competence seems deficient in children with borderline IDs, who struggle with distancing themselves from their own perspective to understand what others know ( Baglio et al, 2016 ). Finally, Légaré et al (2019) observed that mothers also perceived difficulties in both affective and cognitive ToM competence in their children with IDs, compared with parents of typically developing children.…”
Section: Introductionmentioning
confidence: 95%